MEMBANGUN COMPETITIVE ADVANTAGE MELALUI BRAND IMAGE "THE PREMIUM OF INSPIRE" UNTUK MENARIK MINAT SISWA PADA LKP INSPIRE PARE - ARRIDHO, MOH. BASIT; Zulistiani, Zulistiani; Damayanti, Susi (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2023)
The background of this research is an English course institution that builds competitive advantage through the brand image to attract students' interest, where the object of research is LKP Inspire Pare. The purpose of this research is to analyze whether the brand image owned by LKP Inspire Pare is able to build a competitive advantage and can attract students' interest. Furthermore, the method used in this study is a qualitative method with a phenomenological approach. Data collection techniques in this study are through observation, interviews, and documentation. Data analysis techniques used, data reduction, data presentation, and drawing conclusions or verification will then be tested for the validity of the data using the source triangulation method and method triangulation. The conclusion of this study is knowing that LKP Inspire Pare has a brand called The Premium of Inspire which is supported by premium services, programs, and services so that it can build competitive advantage and attract students' interest.